METHODOLOGY OF DIFFERENTIATED FINGER TRAINING FOR ARMRESTLERS OF INITIAL TRAINING GROUPS - Nikulin, I.N.; Ahmedshin, I.G.; Posokhov, A.V.; Ruchnov, A.M. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a methodology for differentiated training of finger strength in armwrestlers aged 10-13 and to determine its effectiveness. Methods and structure of the study. The experiment involved 32 arm wrestlers aged 10-13 years old in the weight categories 50 and 55 kg, with 0.5-1 year of training experience, without categories. Of these, 16 were the control and 16 experimental group. Tensodynamometry was used as the main testing method. The results of maximum efforts were recorded in the following basic anatomical movements of the young armwrestler's strength topography: finger flexors, four-finger flexors alternately (except for the thumb). Between the mount and the chain is a Grant Scalse brand electronic dynamometer to record the maximum force exerted by the test subject on the handle in static mode. Results and conclusions. The study of the indicators of the strength of the muscles - the flexors of the fingers and its dynamics in arm wrestlers aged 10-13 years old in the initial training groups under the conditions of the formative experiment showed a more significant increase in the results in the experimental group. The greatest increase was established in terms of “Dynamometry of the strength of the middle finger” both on the left and on the right hand (p<0.01). Presumably, this is due to the fact that the middle finger, according to testing, is the strongest of all the fingers of the hand and therefore, in all complex exercises for hand strength, it receives the greatest load compared to other fingers. The use of differentiated finger training can become a predictor of an increase in the effectiveness of competitive activity, which deserves attention and further study.